2020
DOI: 10.1038/s41529-020-00126-5
|View full text |Cite
|
Sign up to set email alerts
|

How build angle and post-processing impact roughness and corrosion of additively manufactured 316L stainless steel

Abstract: Additively manufactured austenitic stainless steels exhibit numerous microstructural and morphological differences compared to their wrought counterparts that will influence the metals corrosion resistance. The characteristic as-printed surface roughness of powder bed fusion (PBF) stainless steel parts is one of these morphological differences that increases the parts susceptibility to localized corrosion. This study experimentally determines the average surface roughness and breakdown potential (E b) for PBF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 98 publications
(150 reference statements)
0
31
0
2
Order By: Relevance
“…[112][113] The few corrosion studies that have directly examined asbuilt AM surfaces have found severely diminished resistance relative to conventionally processed material and attributed this to the crevice-like geometry of surface porosity. 18,[114][115][116] A recent study by Melia, et al, found that the average breakdown potentials of SLM 316L as-built surfaces were at least 400 mV lower than a polished surface of the same material in 0.6 M NaCl. 116 Furthermore, E b varied widely with surface inclination angle with the rough downskin surfaces averaging 550 mV lower than the best performing and smooth upskin surfaces, Figure 14.…”
Section: Printed Surface Defectsmentioning
confidence: 99%
See 4 more Smart Citations
“…[112][113] The few corrosion studies that have directly examined asbuilt AM surfaces have found severely diminished resistance relative to conventionally processed material and attributed this to the crevice-like geometry of surface porosity. 18,[114][115][116] A recent study by Melia, et al, found that the average breakdown potentials of SLM 316L as-built surfaces were at least 400 mV lower than a polished surface of the same material in 0.6 M NaCl. 116 Furthermore, E b varied widely with surface inclination angle with the rough downskin surfaces averaging 550 mV lower than the best performing and smooth upskin surfaces, Figure 14.…”
Section: Printed Surface Defectsmentioning
confidence: 99%
“…18,[114][115][116] A recent study by Melia, et al, found that the average breakdown potentials of SLM 316L as-built surfaces were at least 400 mV lower than a polished surface of the same material in 0.6 M NaCl. 116 Furthermore, E b varied widely with surface inclination angle with the rough downskin surfaces averaging 550 mV lower than the best performing and smooth upskin surfaces, Figure 14. Inclination angle dependence was attributed to the relative amounts and nature of the crevice-like porosity, as exemplified in Figure 13.…”
Section: Printed Surface Defectsmentioning
confidence: 99%
See 3 more Smart Citations